2004
DOI: 10.1117/1.1689336
|View full text |Cite
|
Sign up to set email alerts
|

Resonance Raman spectroscopy of optically trapped functional erythrocytes

Abstract: We introduce a novel setup combining a micro-Raman spectrometer with external optical tweezers, suitable for resonance Raman studies of single functional trapped cells. The system differs from earlier setups in that two separate laser beams used for trapping and Raman excitation are combined in a double-microscope configuration. This has the advantage that the wavelength and power of the trapping and probe beam can be adjusted individually to optimize the functionality of the setup and to enable the recording … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
68
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 22 publications
0
68
0
Order By: Relevance
“…In some studies, the cells were immobilized by methanol fixation on a glass slide in air (27) and adsorbed on polylysine-coated glass surfaces (33). In addition, Raman spectra have been obtained from individual optically trapped cells by using different excitation lines (34). Those studies demonstrated the potential for Raman spectroscopy in the study of red blood cell disorders such as thalassemia, sickle cell disease, and malaria.…”
Section: In Vivo Measurementsmentioning
confidence: 99%
See 3 more Smart Citations
“…In some studies, the cells were immobilized by methanol fixation on a glass slide in air (27) and adsorbed on polylysine-coated glass surfaces (33). In addition, Raman spectra have been obtained from individual optically trapped cells by using different excitation lines (34). Those studies demonstrated the potential for Raman spectroscopy in the study of red blood cell disorders such as thalassemia, sickle cell disease, and malaria.…”
Section: In Vivo Measurementsmentioning
confidence: 99%
“…Previous studies on isolated red blood cells have shown that the type of glass coating and the laser irradiation had an important influence on the Raman spectra (33,34). Cells may lose their intrinsic shape as result of substrate-induced effects and photo-induced effects when Raman spectroscopy is used (32,34).…”
Section: Limitations and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technique allowed much more detailed investigations of hemoglobin, and many of the early demonstrations of LTRS were performed using RBCs as samples. [54][55][56][57] As LTRS technology has matured, it has been used to refine previous studies that had experienced limitations due to sampling protocols. Dasgupta 58 These bands were consistent with hemoglobin existing in an aggregated form, confirming earlier work by researchers from the Monash Figure 3.…”
mentioning
confidence: 99%